Fundamentals of rational emotive behaviour therapy a training handbook - Dryden, Windy (John Wiley & Sons Ltd, 2024)
"The only book that seeks to provide therapists with REBT skills in a training format. The book reflects the work Windy Dryden did running the Masters in REBT at Goldsmiths University from 1995-2014. The new edition reflects the changing language in REBT (from irrational-rational beliefs to rigid/extreme-flexible/non-extreme attitudes). All training methods are updated where appropriate and new material has been included reflecting the growing emphasis in REBT of the working alliance and data on client visits"-- Provided by publisher.